Job satisfaction among teachers in selected vocational colleges in the state of Selangor - Che Huhaimi, Siti Aishah (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Job satisfaction can be one of the most important factor that can contribute to an individual effectiveness and performance in an organization. Job satisfaction can be defined as an individual emotional condition regarding his or her job and can be referred to what that individual can get from the job and the expectation and contentment of that individual has towards the job. Same as in educational system, job satisfaction among teachers need to be considered and measured in order to know what are the important factors that can contribute to teachers high job satisfaction level and does teacher job satisfaction have significant effect towards their teaching performances. The main objective of this research is to identify the level of job satisfaction among vocational teachers in some selected vocational colleges. This research will be conducted using survey questionnaires that will be constructed as the instrument for this research design by referring to Minnesota Satisfaction Questionnaires. The sample size of this research will be comprised of 160 vocational teachers from two vocational colleges in the state of Selangor. The level of job satisfaction among the vocational teachers will be measured based on several factors including demographic factors which consists of age, gender and years of teaching experience and other factors including workplace conditions, administrative support, students characteristics, recognition and school management.